Closing the Relevance Gap: Lessons in Co-Developing Gender Transformative Research Approaches with Development Partners and Communities - Ferdous, N.; Jost, Christine; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Theme Linking Knowledge with Action (K2A) engaged in a two-year social learning process to develop tools, best practices and capacity building trainings around gender sensitive and participatory research for climate change. The output was the resource guide, “Gender and Inclusion Toolbox: Participatory Research in Climate Change and Agriculture”. This paper documents the social learning process of co-designing and co-testing the toolbox with various development partners, CGIAR scientists, technical officers and local communities and offers key reflections and learning on the challenges and entry points to promoting a participatory and gender sensitive research agenda across upstream and downstream stakeholders.